Bioavailabilities of Quercetin-3-Glucoside and Quercetin-4′-Glucoside Do Not Differ in Humans - Olthof, Margreet R.; Hollman, Peter C.H.; Vree, Tom B.; Katan, Martijn B. (The Journal of nutrition, 2000)
The flavonoid quercetin is an antioxidant which occurs in foods mainly as glycosides. The sugar moiety in quercetin glycosides affects their bioavailability in humans. Quercetin-3-rutinoside is an important form of quercetin in foods, but its bioavailability in humans is only 20% of that of quercetin-4′-glucoside. Quercetin-3-rutinoside can be transformed into quercetin-3-glucoside by splitting off a rhamnose molecule. We studied whether this 3-glucoside has the same high bioavailability as the quercetin-4′-glucoside. To that end we fed five healthy men and four healthy women (19–57 y) a single dose of 325 μmol of pure quercetin-3-glucoside and a single dose of 331 μmol of pure quercetin-4′-glucoside and followed the plasma quercetin concentrations. The bioavailability was the same for both quercetin glucosides. The mean peak plasma concentration of quercetin was 5.0 ± 1.0 μmol/L (±se) after subjects had ingested quercetin-3-glucoside and 4.5 ± 0.7 μmol/L after quercetin-4′-glucoside consumption. Peak concentration was reached 37 ± 12 min after ingestion of quercetin-3-glucoside and 27 ± 5 min after quercetin-4′-glucoside. Half-life of elimination of quercetin from blood was 18.5 ± 0.8 h after ingestion of quercetin-3-glucoside and 17.7 ± 0.9 h after quercetin-4′-glucoside. We conclude that quercetin glucosides are rapidly absorbed in humans, irrespective of the position of the glucose moiety. Conversion of quercetin glycosides into glucosides is a promising strategy to enhance bioavailability of quercetin from foods.